Mid- and far-infrared data for the analysis of Australian plant exudatesFigshare private link - Abigail K. Mann; Dominique Appadoo; Claire E. Lenehan; Rachel S. Popelka-Filcoff (Data in Brief, 2025)
Plant exudates have been used around the world for cultural expression and various applications throughout the archaeological record and continue today. Indigenous Australians utilize specific plant exudates for their physiochemical properties and as a fundamental connection to Country. This manuscript contains data related to the analysis of aged Australian native plant exudates, using an assemblage from turn of the 20th century with provenance information but no further information on the collectors. Data from these aged samples are augmented by parallel examples from worldwide locations that have been more extensively characterized. Data were acquired via laboratory-based mid-infrared spectroscopy (mid-IR) and synchrotron-based far-infrared spectroscopy (far-IR). Spectral data are presented, organised by genera with multiple samples (Xanthorrhoea, Aracauria, Acacia, Callitris, Eucalyptus) for both mid- and far-IR regions to allow direct comparisons of the fingerprint areas for both spectral regions. All spectra were normalised to their highest and lowest values for presentation. Further comparisons can be made with future work on native Australian plant exudates in collections and cultural heritage materials, to identify their genera and species. This manuscript presents the collected spectral data in the mid and far infrared.